Preparing biomedical students for the unknown: Some unusual challenges for students to help them understand the fundamentals of empirical research. (15th September 2019) - Rivero‐Müller, Adolfo; Nees, Matthias
Abstract : Make teaching challenging again: a pedagogic approach to educate students on how to do science rather than learn about it.